MENGGUGAH SPIRIT GURU DALAM MEMANFAATKAN MEDIA PEMBELAJARAN - Z. Mahmudah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2012)
Abstract : Instructional aids are all the things which are used to deliver school materials to stimulate student’s attention, interest, mind, and feeling for objective attainment. Success of learning process depends on teacher’s enthusiasm to utilize instructional aids. Key Words: Teacher, Learning, and Aids.